2022
DOI: 10.1111/andr.13233
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric ultrasound for the diagnosis of Leydig cell tumours in non‐palpable testicular lesions

Abstract: Background:The widespread use of ultrasonography has led to an increased number of incidentally detected small non-palpable lesions, with Leydig cell tumours representing the majority of them. Objectives:The ultrasonography, real-time elastography and contrast-enhanced ultrasonography features of a large series of non-palpable testicular lesions were evaluated, focusing on the differences between Leydig cell tumours and other testicular masses. Materials and methods:Of the 4679 testicular ultrasonography exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 69 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…This is consistent with our findings (Table 1), where hormonal disturbances seem to be the main reason for patients with LCT to seek medical attention, rather than testicular pain. Carmignani L 18 also reported a 43% incidence of LCT in patients with testicular tumors referred for infertility, while Corcioni B 19 found a 49.2% incidence in a similar study, highlighting a close association between high incidence rates and referral centers for infertility. In pediatric patients with LCT, signs of precocious puberty appear to be more common, such as rapid growth acceleration, advanced bone age, and early appearance of secondary sexual characteristics.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This is consistent with our findings (Table 1), where hormonal disturbances seem to be the main reason for patients with LCT to seek medical attention, rather than testicular pain. Carmignani L 18 also reported a 43% incidence of LCT in patients with testicular tumors referred for infertility, while Corcioni B 19 found a 49.2% incidence in a similar study, highlighting a close association between high incidence rates and referral centers for infertility. In pediatric patients with LCT, signs of precocious puberty appear to be more common, such as rapid growth acceleration, advanced bone age, and early appearance of secondary sexual characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…When LCT are larger or atypical, they may show heterogeneous enhancement, but most LCT demonstrate slow washout in the late phase of contrast imaging. Corcioni B 19 also analyzed contrast‐enhanced ultrasound in 32 LCT patients and 33 non‐LCT patients, and found that 96.9% of LCT showed a pattern of rapid enhancement followed by slow washout, with clearer margins compared to non‐LCT tumors. They also attributed this enhancement pattern to the rich vascularity both peripherally and internally in LCT, which may help differentiate them from seminomas characterized by irregular neovascularization and presence of necrotic areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPI, TPI/MPI and AUTIC, which represent the microcirculation perfusion of tumors ( 17 ), showed significant differences in benign and malignant tumors. However, there was no difference in TPK and slope value between the benign and malignant groups, the two CEE parameters represent tumor blood perfusion velocity and may be related to the increase in neovascularization in malignant tumors ( 18 ). Necrosis may occur inside some large and fast-growing malignant tumors without sufficient blood supply, which affects the peak intensity measurement ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elastography of the scrotum is easily and rapidly performed without any additional discomfort to the patient. Both SE and SWE have been used in the assessment of testicular lesions [ 49 , 51 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. SE elastography aims to assess tissue stiffness by quantifying tissue deformation, whereas SWE measures the speed of propagation when applying force [ 17 , 63 ].…”
Section: Scrotummentioning
confidence: 99%